Nose-only inhalations of high-dose alumina nanoparticles/hydrogen chloride gas mixtures induce strong pulmonary pro-inflammatory response: a pilot study. (6th December 2021) - Bourgois, Alexandra; Saurat, Dominique; De Araujo, Suzanne; Boyard, Alexandre; Guitard, Nathalie; Renault, Sylvie; Fargeau, Francisca; Frederic, Christine; Peyret, Emmanuel; Flahaut, Emmanuel; Servonnet, Aurélie; Favier, Anne-Laure; et al.
Abstract: Objective: Solid composite propellants combustion, in aerospace and defense fields, can lead to complex aerosols emission containing high concentrations of alumina nanoparticles (Al2 O3 NPs) and hydrogen chloride gas (HClg ). Exposure to these mixtures by inhalation is thus possible but literature data toward their pulmonary toxicity are missing. To specify hazards resulting from these combustion aerosols, a pilot study was implemented. Materials and methods: Male Wistar rats were nose-only exposed to Al2 O3 NPs (primary size 13 nm, 10 g/L suspension leading to 20.0–22.1 mg/m 3 aerosol) and/or to HClg aerosols (5 ppm target concentration) following two exposure scenarios (single exposures (SE) or repeated exposures (RE)). Bronchoalveolar lavage fluids (BALF) content and lungs histopathology were analyzed 24 h after exposures. Results: Repeated co-exposures increased total proteins and LDH concentrations in BALF indicating alveolar–capillary barrier permeabilization and cytolysis. Early pulmonary inflammation was induced after RE to Al2 O3 NPs ± HClg resulting in PMN, TNF-α, IL-1β, and GRO/KC increases in BALF. Both exposure scenarios resulted in pulmonary histopathological lesions (vascular congestions, bronchial pre-exfoliations, vascular and interalveolar septum edemas). Lung oxidative damages were observed in situ following SE. Conclusion: Observed biological effects are dependent on both aerosol content and exposure scenario. Results showed an important pro-inflammatory effect of Al2 O3 NPs/HClg mixtures on the lungs of rat 24 h after exposure. This pilot study raises concerns toward potential long-term pulmonary toxicity of combustion aerosols and highlights the importance for further studies to be led in order to define dose limitations and exposure thresholds for risk management at the work place.